Detection of Colistin Resistance in Pseudomonas aeruginosa Using the MALDIxin Test on the Routine MALDI Biotyper Sirius Mass Spectrometer - Jeannot, Katy; Hagart, Katheryn; Dortet, Laurent; Kostrzewa, Markus; Filloux, Alain; Plesiat, Patrick; Larrouy-Maumus, Gerald (Frontiers in Microbiology, 2021)
Colistin is frequently a last resort treatment for Pseudomonas aeruginosa infections caused by multidrug-resistant (MDR) and extensively drug resistant (XDR) strains, and detection of colistin resistance is essential for the management of infected patients. Therefore, we evaluated the recently developed MALDIxin test for the detection of colistin resistance in P. aeruginosa clinical strains using the routine matrix-assisted laser desorption ionization (MALDI) Biotyper Sirius system. The test is based on the detection by mass spectrometry of modified lipid A by the addition of 4-amino-l-arabinose (l-ara4N) molecules on one or two phosphate groups, in strains resistant to colistin. Overproduction of l-Ara4N molecules is mainly due to the constitutive activation of the histidine kinase (PmrB) or the response regulator (PmrA) following an amino-acid substitution in clinical strains. The performance of the test was determined on a panel of 14 colistin-susceptible and 14 colistin-resistant P. aeruginosa clinical strains, the reference strain PAO1 and positive control mutants PmrB (V28G), PmrB (D172), PhoQ (D240–247), and ParR (M59I). In comparison with the broth microdilution (BMD) method, all the susceptible strains (n=14) and 8/14 colistin-resistant strains were detected in less than 1h, directly on whole bacteria. The remaining resistant strains (n=6) were all detected after a short pre-exposure (4h) to colistin before sample preparation. Validation of the method on a larger panel of strains will be the next step before its use in diagnostics laboratories. Our data showed that the MALDIxin test offers rapid and efficient detection of colistin resistant P. aeruginosa and is thus a valuable diagnostics tool to control the spread of these emerging resistant strains.